Understanding Large-Scale Structure in Global Ionospheric Maps With Visual and Statistical Analyses - Verkhoglyadova, Olga; Meng, Xing; Kosberg, Jacob (Frontiers in Astronomy and Space Sciences, 2022)
We applied two different techniques to identify high-density structures in global maps of height-integrated electron density of the Earth’s ionosphere. We discuss benefits and limitations of these approaches to structure identification. We suggest that they are complementary and can aid our understanding of the properties of the global ionosphere. We stress out importance of a consistent definition of large-scale ionospheric structures.